PENGARUH KUALITAS PELAYANAN DAN PRODUK TERHADAP KEPUASAN KONSUMEN INDUSTRI BATU ALAM DI WILAYAH TULUNGAGUNG - Siga Tridiantoro; Maria Agatha SWH (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2023)
In this modern era, the business world is growing very rapidly and experiencing changes in the form of creating increasing competition. Especially in a natural stone industry must win a competition. Understanding what consumers want will have its own value for the industry owner. This study aims to determine: the effect of service quality and product quality on customer satisfaction in the natural stone industry at UD Zige Stone in the Ngentrong Village area, Campurdarat District, Tulungagung Regency. This research uses quantitative with a descriptive approach. The test data is primary data. The population of the research conducted by this researcher were all consumers of natural stone, using random sampling method. Data collection techniques using a questionnaire. The data analysis tool used is SPSS data analysis. The results of this study indicate that: 1. Based on the results of the evaluation of the measurement model that the variables X1, X2 and Y are declared valid. 2. Based on the results of hypothesis testing, the service quality and product quality variables have a significant influence on consumer satisfaction variables.